A Case Study of K-8 Students’ Problem-Solving Skill on Pressure Subject - Wijayatno, Matius Heru; Rusdiana, Dadi (International Conference on Multidisciplinary Research, 2020)
This study aimed to get a general picture of K-8 students’ problem-solving skills on pressure subjects. This study employed a qualitative method with a case study approach. Moreover, students’ problem-solving skills were measured based on stages of visualization/problem description, physical approach, particular physical application, mathematical procedure, and logical conclusion. The samples of this study were 30 K-8 students in a private school in Bandung. This study showed that students’ problem-solving skills at each stage were different. Nevertheless, the overall results were categorized into moderate.  Keywords: problem solving skill, skill, pressure